Penatalaksanaan Senam Kaki Diabetik pada Keluarga Diabetes Mellitus untuk Mencegah Komplikasi - Dewi Suciningtyas, Putri, Warchidah Yuniartika, S.Kep., Ns., M.Kep (2017)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia associated with abnormalities in the metabolism of carbohydrates, fats, and proteins caused by a decrease in insulin secretion or decreased sensitivity or both and causing chronic complications of microvascular, macrovascular, and neuropathy. Indonesia has one of the entrance to the country that the prevalence of diabetes is also increasing and is expected in 2025 Indonesia Diabetes Mellitus in the fifth. Giving activity gymnastics diabetic foot is one of the effective ways to manage diabetes and prevent complications objective of this study is the researchers were able to conduct assessments for Mrs. S, researchers were able to formulate nursing diagnoses for Mrs. S, researchers are able to develop interventions for Mrs. S, researchers were able to implement the Ny S, researchers were able to do an evaluation of Mrs. S, the researchers were able to analyze the results of diabetic foot gymnastics action to improve sensitvity feet in patients with diabetes mellitus type 2. this research method using descriptive method through case studies. A case study using case study method is guided by the nursing process that includes assessment, data analysis, nursing diagnosis, intervention and implementation. The results of this study, the Family Mr. H says no understanding of the disease Diabetes Mellitus, signs and symptoms of complications from Diabetes Mellitus, and Mrs S said numb, stiff, around the lower leg, can not walk far, was seen Mrs S grimacing in pain and pain. The diagnoses that researchers take is the inability of families caring for family members with diabetes mellitus associated with lack of family knowledge about how to prevent the treatment of diabetes mellitus. Researchers taught gymnastics diabetic foot against diabetes mellitus family regularly using leafleat media and newspapers. With regular exercise diabetic foot numbness, stiffness around the lower leg is reduced, with proven client was able to walk away, and say the numbness and stiffness around the legs is reduced.